2020
DOI: 10.22541/au.160937136.67710116/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Central Histaminergic Signaling, Neural Excitability and Epilepsy

Abstract: Epilepsy is a common neurological disorder characterized by repeated and spontaneous epileptic seizures, which is not well controlled by current medication. Traditional theory supports that epilepsy results from the imbalance of excitatory glutamate neurons and inhibitory GABAergic neurons. Recently, shreds of evidence from available clinical and preclinical researches suggest that histamine in the central nervous system plays an important role in the modulation of neural excitability and pathogenesis of epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 115 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…The histaminergic system comprises genes coding histamine receptors and enzymes involved in the metabolism of histamine. Additionally, the histaminergic system interacts with other neural systems, including the dopaminergic [ 5 ], GABAergic [ 6 ], opioidergic [ 7 ], noradrenergic [ 40 ], and angiotensynergic systems [ 41 ], which was confirmed using the PANTHER database [ 42 ]. The findings of this study also suggested that the inflammatory condition modulates the histaminergic system and that the histaminergic system-associated genes are involved in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histaminergic system comprises genes coding histamine receptors and enzymes involved in the metabolism of histamine. Additionally, the histaminergic system interacts with other neural systems, including the dopaminergic [ 5 ], GABAergic [ 6 ], opioidergic [ 7 ], noradrenergic [ 40 ], and angiotensynergic systems [ 41 ], which was confirmed using the PANTHER database [ 42 ]. The findings of this study also suggested that the inflammatory condition modulates the histaminergic system and that the histaminergic system-associated genes are involved in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HRH4, which is coupled with the Gi protein, downregulates the levels of adenosine 3’ 5’-cyclic monophosphate (cAMP). The functions of the histaminergic system are independent of external stimuli irrespective of the receptor type that is activated [ 3 , 6 , 7 ]. Psoriasis is a chronic, multi-factor, inflammatory skin disease with a complex immunopathogenesis.…”
Section: Introductionmentioning
confidence: 99%